(untitled) (Scientific journal of the Fergana State University, 2024)
This article is dedicated to the encyclopedist scholar Abu Ali Ibn Sina and his great scientific legacy. Ibn Sina’s heritage is considered a spiritual treasure of the peoples of the world. His rich heritage has not been studied enough. Especially waiting for the researcher of his works on the sciences of tafsir, mysticism and logic. In the article, Ibn Sina’s attitude to Sufism is analyzed on the basis of wide and reliable sources.